2013
DOI: 10.2174/15748863113089990036
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatraemia: An Audit of Aged Psychiatry Patients Taking SSRIs and SNRIs

Abstract: These data suggest that antidepressant treatment is associated with hyponatraemia affecting a subgroup of individuals only. Generalised linear modelling showed that the risk of hyponatraemia increases with increased age, female gender, and particularly the antidepressant agents sertraline and escitalopram. The findings are of clinical significance as they demonstrate that hyponatraemia can occur rapidly with antidepressants, and SSRI/SNRI medications induce more rapid changes. They support the use of electroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
5

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 0 publications
1
21
0
5
Order By: Relevance
“…86 cases of sertraline showed hyponatremia [5]. An audit of aged psychiatric patients using SSRI and SNRI showed that risk of hyponatremia is more with increasing age, female gender and more commonly associated with escitalopram and sertraline [10]. A very recent study has shown a higher prevalence of hyponatremia in patients with depression who are being prescribed SSRI and SNRI [11].…”
Section: Discussionmentioning
confidence: 99%
“…86 cases of sertraline showed hyponatremia [5]. An audit of aged psychiatric patients using SSRI and SNRI showed that risk of hyponatremia is more with increasing age, female gender and more commonly associated with escitalopram and sertraline [10]. A very recent study has shown a higher prevalence of hyponatremia in patients with depression who are being prescribed SSRI and SNRI [11].…”
Section: Discussionmentioning
confidence: 99%
“…Os sintomas raramente surgem antes do Na + sérico descer para valores inferiores a 130 mEq/L e dependem da gravidade da hiponatremia (Tabela 2). A hiponatremia normalmente ocorre nas primeiras 10 semanas de tratamento e 79% dos casos nas primeiras três semanas 9 . Entre os fatores de risco de hiponatremia, encontram-se idade, sexo feminino, utilização de medicação concomitante que provoque hiponatremia (antidiabéticos, anti-inflamatórios não esteroides, anticonvulsivantes e, principalmente, os diuréticos tiazídicos e inibidores da enzima conversora de angiotensina -IECA), história de pneumonia recente e perturbação do humor, estando os três primeiros associados também a hiponatremia mais severa 1,6,10 .…”
Section: Métodosunclassified
“…A dieta com restrição de sódio concomitante também pode potenciar o desenvolvimento de hiponatremia 12 . Pensa-se que os ADs podem provocar a estimulação direta ou indireta da libertação de ADH, possivelmente mediante a estimulação da serotonina com atividade aumentada, ou que modulam a ação da ADH no rim causando retenção de água e hiponatremia 7,9,11,13 . Os critérios de diagnóstico de SIADH podem ser encontrados na Tabela 3.…”
Section: Mecanismo Da Hiponatremiaunclassified
“…Giorlando et al, in a retrospective study from 2013, found that risk factors for hyponatremia following SSRI and SNRI were age > 65 years, female sex and sertraline or escitalopram use [37]. Other risk factors for hyponatremia include past events of hyponatremia in the patient, body weight <60 kg, psychotic symptoms [31], female sex [25] and antidepressant combination with diuretics, angiotensin converting enzyme inhibitors (ACEI) or inhibitors of protonic pump (IPP) [34].…”
Section: Siadh and Antidepressantsmentioning
confidence: 99%
“…Retrospektywne badanie z 2013 roku przeprowadzone przez Giorlando i wsp. wykazało, że do czynników ryzyka wystąpienia hiponatremii po zastosowaniu leków z grupy SSRI i SNRI należą wiek > 65 roku życia, płeć żeńska oraz zastosowanie sertraliny lub escitalopramu [37]. Wśród innych czynników ryzyka rozwoju hiponatremii można występowanie hiponatremii u pacjenta w przeszłości, masę ciała < 60kg, obecność objawów psychotycznych [31], płeć żeńską [25] oraz stosowanie leków przeciwdepresyjnych w skojarzeniu z diuretykami, inhibitorami konwertazy angiotensyny (ACEI) lub inhibitorami pompy protonowej (IPP) [34].…”
Section: Przyczynyunclassified